A Scoping Review of Positive Lifestyle and Wellness Interventions to Inform the Development of a Comprehensive Health Promotion Program: "HealthPro". Issue 4 (July 2019) - Schuette, Stephanie A. P.; Cordero, Evelyn; Slosburg, Katherine; Addington, Elizabeth L.; Victorson, David
Background . Lifestyle medicine has emerged as a transformational force in mainstream health care. Numerous health promotion and wellness programs have been created to facilitate the adoption of increased positive, modifiable health behaviors to prevent and lessen the effects of chronic disease. This article provides a scoping review of available health promotion interventions that focus on healthy adult populations in the past 10 years. Methods . We conducted a scoping review of the literature searching for health promotion interventions in the past 10 years. Interventions were limited to those conducted among healthy adults that offered a face-to-face, group-based format, with positive results on one or more health outcomes. We then developed a new health promotion intervention that draws on multiple components of included interventions. Results . Fifty-eight articles met our inclusion criteria. Physical activity was the primary focus of a majority (N = 47) of articles, followed by diet/nutrition (N = 40) and coping/social support (N = 40). Conclusions . Efficacious health promotion interventions are critical to address the prevention of chronic disease by addressing modifiable risk factors such as exercise, nutrition, stress, and coping. A new intervention, discussed is this article, provides a comprehensive approaches to health behavior change and may be adapted for future research.